Staff Member Perceptions of Bullying in an Afterschool Center - Thegg, Sherrich Monsher (2017)
Peer-to-peer bullying negatively impacts over 20% of school-aged children annually. While much literature exists on bullying on school premises, peer-to-peer bullying outside of the classroom is still relatively understudied. Despite states' implementation of antibullying legislation, peer-to-peer bullying has continued in schools and other areas such as afterschool centers. The purpose of this qualitative study was to evaluate staff perceptions of peer-to-peer bullying in afterschool centers. It specifically investigated bullying and the hierarchical imbalance of power using Sidanius and Pratto's social dominance theory. The research questions were designed to investigate the staff members' knowledge of bullying at the Boys and Girls Club. A phenomenological approach was used and data were collected through one-on-one interviews of 11 Boys and Girls Club staff members. Data from the interviews were deductively coded and subjected to thematic analysis. Findings indicate that staff members do not have a uniform understanding of bullying behaviors, nor did they have a clear guidance on practices to minimize bullying which leads to continued peer-to-peer bullying at the Boys and Girls Club. Staff also reported that they have been offered little training on dealing with bullying behavior, nor are there clear policies in place to combat bullying behavior from participants in the afterschool program. Positive social change may be achieved by the implementation of recommendations to the Boys and Girls Club including mandatory antibullying training for staff and the creation and implementation of a comprehensive antibullying policy